Wind erosion researches in Hungary – past, present and future possibilities - Négyesi, Gábor; Lóki, József; Buró, Botond; Bertalan-BalázsBoglárka; Pásztor, László (Hungarian Geographical Bulletin, 2019)
Wind erosion is one of the most important land degradation processes in Hungary in the areas with low yearly precipitation values. The total land area suffering from wind erosion is approximately 10,000 km2, 10 per cent of the country area. Observations and discussions on wind erosion and its negative impacts in Hungary started in the last century. Since the 1950s, scientists investigated wind erosion processes and its role in the evolution of alluvial fans in an integrative way, including laboratory measurements and field observations with respect to the stabilization and utilization of soils in agricultural areas. Since the late 2000s, there is an increasing demand worldwide to characterize the role of climate change and human activities in triggering land degradation processes. Studies have been conducted to investigate the mechanics, causes and control techniques related to wind erosion applying laboratory and field wind tunnel simulation tests and field observations. Some encouraging achievements have been made. In this paper we summarize the main research results of wind erosion research, and put forward some perspectives and suggestions on the problems of wind erosion research and control practices in Hungary.